2010
DOI: 10.1097/shk.0b013e3181cdc398
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14 PROSTAGLANDIN GJ2 BUT NOT ROSIGLITAZONE REGULATES METALLOPROTEINASE 9, NOS-2, AND CYCLOOXYGENASE 2 EXPRESSION AND FUNCTIONS BY PEROXISOME PROLIFERATORYACTIVATED RECEPTOR Γ-Dependent AND -INDEPENDENT MECHANISMS IN CARDIAC CELLS

Abstract: Sepsis or endotoxemia produced by LPS followed by hypotension and multiorganic failure may lead to cardiac dysfunction contributing to mortality. Cardiac failure is usually associated to activation of nuclear factor kappaB (NF-kappaB) and mitogen-activated protein kinase (MAPK), which play an important role in proinflammatory enzymes expression. It has been shown that 15-deoxy-Delta12,14 prostaglandin J2 (15dPGJ2) can repress the inflammatory response by means of peroxisome proliferator-activated receptor gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…From all these reports, it is clear that the effects of rosiglitazone depend not only on the doses of the drug but also on the cell type or the experimental model used. As far as treatment with 15d-PGJ 2 is concerned, our results are in accordance with reports in the literature (16,17).…”
supporting
confidence: 95%
“…From all these reports, it is clear that the effects of rosiglitazone depend not only on the doses of the drug but also on the cell type or the experimental model used. As far as treatment with 15d-PGJ 2 is concerned, our results are in accordance with reports in the literature (16,17).…”
supporting
confidence: 95%
“…Quantification of gene expression was calculated using the comparative threshold cycle (C T ) method, normalized to the 18S control and efficiency of the reverse transcriptase reaction (relative quantity, 2 Ϫ⌬⌬CT ). The replicates were then averaged, and the fold induction was determined, with the value in the control group as 1 (23).…”
Section: Micementioning
confidence: 99%
“…Reports have shown that 15d-PGJ 2 can repress some genes expression through the direct binding of ERK-MAPK and NF κ B [27, 28]. Furthermore, the proinflammatory production of NOS-2, metalloproteinase-2 (MMP-2), and MMP-9 as well as IL-6 and TNF- α in cultured cardiomyocytes infected with Trypanosoma cruzi , a protozoa parasite, was inhibited by administration of 15d-PGJ 2 , but rosiglitazone, a synthetic PPAR- γ agonist, was inefficient in inhibiting such mediators [29].…”
Section: Discussionmentioning
confidence: 99%